Methodological approaches to research and regulation of spatial projection business in depressive regions of Russia - Yu. V. Kuznetsov; V. P. Kaisarova (Вестник университета)
The exogenous and endogenous fundamental approaches of the leading scientists to the models of business density regulation in the regions has been considered. It has been shown, that the management of depressed regions in Russia requires a comprehensive assessment of the complex of enterprises (large, medium and small) based on the assessment of their strategic stability. The study is aimed aimed at solving the problems of substantiation ofproposals for the regulation of spatial heterogeneity and density of economic activity with the integration of efforts of enterprises for their strategic stability and measures of Federal and regional authorities, assessing the potential of depressed regions of Russia. The scientific tools, measures to regulate the density of economic activity of enterprises in the depressed region for their implementation in strategic documents on the example of the Pskov region have been substantiated.